Framework for Building India’s Indigenous Technology Product Development Leadership - Patil, Mahesh (Digital Repository of Theses, 2024)
The destiny of nations is intricately woven with their history, pivotal moments, and evolving factors. Despite India's rich past and recent strides in innovation, gaps persist in harnessing its potential for product development leadership. This research aims to bridge this divide by examining the challenges and opportunities facing Indian companies in achieving product innovation excellence. The literature review highlights a scarcity of comprehensive studies on building sustainable product ecosystems in India, despite extensive research on related fields such as R&D, software services, and manufacturing. While India boasts successes in software services, a disconnect exists between these achievements and local market needs. Additionally, challenges in sectors like electric vehicles (EVs) underscore the need for holistic approaches to product development. To address these gaps, a mixed method approach combining qualitative and quantitative analysis is adopted. Qualitative methods include semi-structured discussions and interviews with industry experts, aimed to understand barriers and identify opportunities. A SWOT analysis aids in comprehensively assessing the challenges in electric scooter development and creation of a framework for positioning India as a global leader in this sector. Findings reveal India's potential for indigenous manufacturing, strong domestic market preferences, and supportive government policies. However, challenges such as high initial costs and infrastructure limitations persist. Opportunities lie in technological advancements and growing market demand, while threats include import competition and regulatory uncertainties. Through this research, India's transition from a service-oriented economy to an indigenous product innovation powerhouse is envisioned. By synthesizing insights from academia and industry, this study offers practical recommendations for policymakers, industry stakeholders, and researchers alike, paving the way for India's emergence as a global leader in product development. Overall, this research contributes to a deeper understanding of India's product development landscape and offers strategic insights for driving sustainable growth and innovation in key sectors of electric vehicles